The effect of training volume on lower-body strength - Robbins, D. W.; Marshall, P. W. M.; McEwen, M. (The Journal of Strength and Conditioning Research, 2012)
The objective of this study was to examine the chronic effects on lower-body strength in resistance trained men of performing varying training volumes over 6 weeks. A pretest and posttest design was used to investigate the effects on 1-repetition maximum (1RM) squat strength. Also, 1RM testing was performed at 3 weeks. Participants were randomly assigned to an intensity-matched (80% of 1RM) low (1-SET), moderate (4-SET), or high (8-SET) volume condition. In addition to significant strength increases in all groups at the end of the 6-week period, increases were observed at 3 weeks under the 4- and 8-SET conditions, which were greater than the improvement under the 1-SET condition. At 6 weeks, the magnitude of improvement was significantly greater for the 8-SET, as compared with that of the 1-SET group. The magnitude of improvement elicited in the 4-SET group was not different from that of the 1-SET or 8-SET groups. The results suggest that "high" volumes (i.e., >4 sets) are associated with enhanced strength development but that "moderate" volumes offer no advantage. Practitioners should be aware that strength development may be dependent on appropriate volume doses and training duration.